T cell activation profiles can distinguish gram negative/positive bacterial sepsis and are associated with ICU discharge - Huang, Canxia; Xiong, Hui; Li, Weichao; Peng, Lu; Zheng, Yukai; Liao, Wenhua; Zhou, Minggen; Xu, Ying (Frontiers in Immunology, 2023)
Sepsis is a life-threatening complication resulting from a dysregulated host response to a serious infection, of which bacteria are the most common cause. A rapid differentiation of the gram negative (G-)/gram positive (G+) pathogens facilitates antibiotic treatment, which in turn improves patients’ survival. We performed a prospective, observational study of adult patients in intensive care unit (ICU) unit and underwent the analysis of peripheral blood lymphocyte subsets, cytokines and other clinical indexes. The enrolled 94 patients were divided into no infection group (n=28) and bacterial sepsis group (n=66), and the latter group was subdivided into G- (n=46) and G+ (n=20) sepsis subgroups. The best immune biomarker which differentiated the diagnosis of G- sepsis from G+ sepsis, included activation markers of CD69, human leukocyte antigen DR (HLA-DR) on CD3+CD8+T subset. The ratio of CD3+CD4+CD69+T/CD3+CD8+CD69+T (odds ratio (OR): 0.078(0.012,0.506), P = 0.008), PCT＞0.53 ng/ml (OR: 9.31(1.36,63.58), P = 0.023), and CO2CP＜26.5 mmol/l (OR: 10.99(1.29, 93.36), P = 0.028) were predictive of G- sepsis (versus G+ sepsis), and the area under the curve (AUC) was 0.947. Additionally, the ratio of CD3+CD4+CD69+T/CD3+CD8+CD69+T≤0.2697 was an independent risk factor for poor ICU discharge in G- sepsis patients (HR: 0.34 (0.13, 0.88), P=0.026). We conclude that enhanced activation of T cells may regulate the excessive inflammatory response of G- bacterial sepsis, and that T cell activation profiles can rapidly distinguish G- sepsis from G+ sepsis and are associated with ICU discharge.